Pengaruh Customer Experience dan Customer Value terhadap Repurchase Intention di The Balcone Suites & Resort - Liza Nuryanti; Waryono Waryono (Yayasan Literasi Sains Indonesia, 2025)
This research is motivated by the phenomenon of repurchase intention caused by customer experience and customer value. The purpose of this study is to analyze the influence of customer experience and customer value on repurchase intention at The Balcone Suites & Resort. The research method used in this study is quantitative descriptive research with a causal-associative approach. The population of this study consisted of guests staying at The Balcone Suites & Resort, with a sample size of 120 respondents selected using Purposive sampling techniques. The study instrument used in this study was a questionnaire with a Likert scale. The data obtained were analyzed using SPSS version 26.00 and the results of the analysis are presented in tabular form. The results of this study are: Customer experience is rated 86.5% in the